Avalia????o da ader??ncia de um hospital p??blico estadual ao programa nacional de seguran??a do paciente - Silva, Georgia Kerley da (2016)
Healthcare in Brazil has undergone significant upgrade in the last decades, due to population growth and the increase in the awareness of getting high quality services. However, while there have been positive and considerable changes in the healthcare area, failures in patient safety have emerged as a priority in global health, as they can cause high morbidity and mortality, and can increase hospitalization days and costs. In 2013, the National Patient Safety Plan was published by the Ministry of Health with the purpose of improving the qualification of care in all health facilities in Brazil. The majority of patient safety incidents are preventable. Consequently, their detection and prevention by hospital organizations should be be sought to increase efficiency in health systems. The purpose of this study was to evaluate the adherence of a public hospital in S??o Paulo to the National Patient Safety Program and, therefore to propose improvements to reduce possible failures in healthcare. The approach adopted was a case study. We used semi-structured interviews with the managers of the participant hospital for data collection followed by analysis using an electronic platform (Survey Monkey??). All health managers invited (n=43) participated in the study. Of these 76.7% have been working in the participant hospital for more than 10 years and 70% had a specialization or postgraduate level. However, it was possible to observe that the fundamental concepts about patient safety and protocols of the National Patient Safety Program were not disseminated in the hospital under investigation. There was also lack of actions and training in the hospital evaluated. We also observed that adverse event is the most recognized patient safety incident (71.2%), while other types of incidents were identified by a small number of respondents. These data allow us to conclude that there is underreporting of patient safety incidents in the hospital under study, since the managers were not able to completly identifying them. Whenever a failure is reported, investigation and disclosure of corrective actions are not made in all cases. Finally, the adherence of the participating hospital to the PNSS is incipient and partly explained by the lack of continuous educational measures and the discussion of this issue among managers. As a contribution to the practice, main patient safety processes were mapped according to the National Patient Safety Plan for implementation in the unit evaluated as well as suggestions for staff training and for performance monitoring.